HASTY modulates miRNA biogenesis by linking pri-miRNA transcription and processing - Cambiagno, Damián Alejandro (2021)
HASTY, the plant ortholog of human exportin 5, was proposed to export miRNAs from the nucleus to the cytoplasm, whereas this has long been disputed. This study shows that HASTY, rather than acting as a miRNA cargo protein, promotes miRNA biogenesis by stabilizing a complex between DCL1 and Mediator at MIRNA loci, thereby acting as a linker between pri-miRNA transcription and processing.